What is needed for reducing the greenhouse gas footprint? - Dickhoefer, Uta; Butterbach-Bahl, Klaus; Pelster, David E. (2014)
Livestock production is responsible for a large amount of greenhouse gas (GHG) emissions. However, numerous approaches have been developed to reduce these emissions and thus lower environmental pollution caused by livestock husbandry. This article shows where interventions are possible and which hurdles have to be cleared in implementing the various measures needed.